PRAGMATIC STUDY OF ASSERTIVE AND USAGE DECLARATIVE IN SOME SELECTED SPEECHES FROM (AL-SAHIFA AL-SAJJADIYYA): IN TERMS OF EMEREN ET AL, (2014) (American Journal of Research in Humanities and Social Sciences, 2025)
Claims, assurance, supposition, explication, and specification seem to be an essential part of human nature. As a result, it can be seen in every speech situation.The current study aims to analyze the applicability of Eemeren et al. (2014) 'distribution of speech acts' in some selected rights of Imam Ali bin Al-Hussain (PBUT). Eemeren et al. (2014) ‘distribution of speech acts’, as they propose, are classified into four types (i.e. assertives, directives, commissives, and usage declaratives), hence the selected texts will be analyzed in terms of assertive and usage declarative. These two types are selected specifically as their pragmatic consideration is closely related with the religious speech. Mixed methods are followed in this study. The qualitative method is used to analyze, interpret, and discuss the data; the quantitative method on the other hand, is used to show the extent to which the categories of speech acts are used.The current study comprises three sections; section one is concerned with introducing the preliminaries of the study that include an introduction, the problem, the hypotheses, the objectives, the procedures, the limits, and the significance of the study. Section two includes some sections about the theoretical background of the study. These sections are; the concept of pragmatics, an overview of speech acts theory, and a short biography about Imam Ali bin Al Hussain (PBUT) aspects of speech respectively. Methodological consideration is established within the third section which is ends with the conclusions.